Clinical Characteristics and Prognosis of HER2-0 and HER2-Low-Positive Breast Cancer Patients: Real-World Data from Patients Treated with Neoadjuvant Chemotherapy - Pöschke, Patrik; Fasching, Peter; Adler, Werner; Rübner, Matthias; Beckmann, Matthias; Hack, Carolin; Heindl, Felix; Hartmann, Arndt; Erber, Ramona; Gaß, Paul (Cancers, 2023)
In our study, we observed the long-term survival outcomes investigated for HER2-0 and HER2-low-positive breast cancer patients who received neoadjuvant chemotherapy. Between 1998 and 2020, 10,333 patients with primary breast cancer were treated, including 1373 patients with HER2-0 or HER2-low-positive disease with neoadjuvant chemotherapy. Descriptive analyses were performed, and logistic regression models and survival analyses were calculated for disease-free survival (DFS) and overall survival (OS). Among the 1373 patients, 930 (67.73%) had HER2-low-positive and 443 (32.27%) had HER2-0 tumors. Patients with HER2-0 tumors had a significantly better pathological complete response, 29.25% vs. 20.09%, and pathological complete response/in situ, 31.97% vs. 24.08%, than patients with HER2-low-positive tumors (p < 0.001; p = 0.003), regardless of the hormone receptor (HR) status. No statistically significant differences were observed for the HR-positive (p = 0.315; p = 0.43) or HR-negative subgroups (p = 0.573; p = 0.931). DFS and OS were significantly longer for HR-positive, HER2-low-positive patients (log-rank p = 0.02; p = 0.012). OS was significantly longer for HR-negative, HER2-0 patients (log-rank p = 0.032). No significant DFS differences were found for the HR-negative cohort (log-rank p = 0.232). For the overall cohort, no significant differences were noted between HER2-low-positive and HER2-0 patients, either for DFS (log-rank p = 0.220) or OS (log-rank p = 0.403). These results show different survival outcomes for HER2-0 and HER2-low-positive tumors relative to HR status. These different cohorts can be identified using standardized immunohistochemistry, even retrospectively.
CRIS-Team Scopus Importer:2023-10-20
Keywords: breast cancer; HER2; HER2-0; HER2-low-positive; neoadjuvant therapy; prognosis